Multilevel Governance, Localization, Stakeholders’ Engagement, and Implementation of Sustainable Development Goals in Oromia, Ethiopia (African Multidisciplinary Journal of Research, 2025)
The Sustainable Development Goals (SDGs) provide a universal framework for addressing global challenges, encompassing 17 goals and 169 targets aimed at eradicating poverty, protecting the planet, and promoting prosperity by 2030. Yet, progress remains critically off track. The 2024 SDG Report shows that only 17 percent of targets are on schedule, with Africa experiencing particularly slow advancement. Ethiopia ranks 145th out of 167 countries on the SDG Index, with a score of 55.5, reflecting persistent challenges. Oromia Regional State, the country’s largest and most populous region, is central to Ethiopia’s SDG trajectory but continues to face governance fragmentation, weak localization, resource constraints, and widespread multidimensional poverty. This study examines the interplay of multilevel governance, localization, and stakeholder engagement in shaping SDG implementation in Oromia, with a focus on the People Pillar (Goals 1–5). Grounded in a pragmatist philosophy and informed by systems, governance, and stakeholder theories, the study employed a mixed-methods design. Survey data were collected from 321 respondents through multistage proportionate stratified random sampling, complemented by 15 key informant interviews and document analysis. Quantitative analysis involved descriptive statistics, regression models, and diagnostic tests, while qualitative data were analyzed thematically to capture institutional dynamics and contextual challenges. Multilevel governance showed a positive but statistically weak association with SDG outcomes, underscoring fragile intergovernmental coordination. Localization demonstrated a significant influence but revealed inconsistencies in aligning global indicators with regional priorities, compounded by limited technical and fiscal capacity. Stakeholder engagement emerged as a moderating factor, significantly strengthening the link between localization and implementation. A combined model explained 14.4% of the variance in SDG implementation. In Oromia, SDG implementation level is moderate but fragile: SDG 3 and 4 recorded relative gains, while SDG 1, SDG 2, and SDG 5 faced entrenched barriers. Theoretically, the study refines the Integrated Governance–Localization–Stakeholder Engagement (IL-SE) Model, demonstrating its relevance for SDG implementation. Practically, the study offers recommendations, including institutionalizing multi-stakeholder platforms, enhancing fiscal and technical decentralization, and strengthening integrated planning and monitoring systems. These measures are essential to bridge the gap between policy ambition and developmental outcomes. By depicting Oromia’s experience within global SDG debates, the research contributes to both scholarly discourse and practical pathways for accelerating sustainable development.